PEMBELAJARAN LITERASI KREATIF PADA ANAK USIA DINI DI SEKOLAH ALTERNATIF ANAK JALANAN (SAAJA) - Kayla Shawafira Nasha; Aji Rachmat Hidayat; Zahid Muhammad Ramadan; Ferdyansyah; Assyifa Fadillah; Fitria Farhani Pansuri; Indah Pusvita Sari; Siti Farihah; Lilis Salsabila; Muhammad Anugrah Herman; Aprillia Tri Purwandari (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2022)
In accordance with the third Tri Dharma of Higher Education, namely community service, the responsibility of a student in addition to completing his duties on campus is to transfer, transform, and apply knowledge to the community. This research aims to carry out a community service program through creative literacy learning at the Street Children's Alternative School (SAAJA), South Jakarta. The research method used is qualitative with observation and interviews as approaches in data collection. After communication, creative literacy learning is carried out through training related to learning, skills, and entertainment.  Material delivery is done in the form of listening to presentations, recognizing numbers, counting, simulations and permainan. At the end of the learning activities, an evaluation was conducted through questionnaires to homeroom teachers to see if the activities carried out had an impact on students at SAAJA. As a result, most students improved their communication skills, numeracy, activeness and discipline, and critical thinking.